# -7y+8y=2x+3(x-5)-2x+3

## Simple and best practice solution for -7y+8y=2x+3(x-5)-2x+3 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so dont hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

## Solution for -7y+8y=2x+3(x-5)-2x+3 equation:

Simplifying
-7y + 8y = 2x + 3(x + -5) + -2x + 3
Combine like terms: -7y + 8y = 1y
1y = 2x + 3(x + -5) + -2x + 3
Reorder the terms:
1y = 2x + 3(-5 + x) + -2x + 3
1y = 2x + (-5 * 3 + x * 3) + -2x + 3
1y = 2x + (-15 + 3x) + -2x + 3
Reorder the terms:
1y = -15 + 3 + 2x + 3x + -2x
Combine like terms: -15 + 3 = -12
1y = -12 + 2x + 3x + -2x
Combine like terms: 2x + 3x = 5x
1y = -12 + 5x + -2x
Combine like terms: 5x + -2x = 3x
1y = -12 + 3x
Solving
1y = -12 + 3x
Solving for variable 'y'.
Move all terms containing y to the left, all other terms to the right.
Divide each side by '1'.
y = -12 + 3x
Simplifying
y = -12 + 3x`